Different X‐linked KDM5C mutations in affected male siblings: is maternal reversion error involved?. Issue 3 (23rd March 2016) - Fujita, A.; Waga, C.; Hachiya, Y.; Kurihara, E.; Kumada, S.; Takeshita, E.; Nakagawa, E.; Inoue, K.; Miyatake, S.; Tsurusaki, Y.; Nakashima, M.; Saitsu, H.; et al.
Abstract : Genetic reversion is the phenomenon of spontaneous gene correction by which gene function is partially or completely rescued. However, it is unknown whether this mechanism always correctly repairs mutations, or is prone to error. We investigated a family of three boys with intellectual disability, and among them we identified two different mutations in KDM5C, located at Xp11.22, using whole‐exome sequencing. Two affected boys have c.633delG and the other has c.631delC. We also confirmed de novo germline (c.631delC) and low‐prevalence somatic (c.633delG) mutations in their mother. The two mutations are present on the same maternal haplotype, suggesting that a postzygotic somatic mutation or a reversion error occurred at an early embryonic stage in the mother, leading to switched KDM5C mutations in the affected siblings. This event is extremely unlikely to arise spontaneously (with an estimated probability of 0.39–7.5 × 10 −28 ), thus a possible reversion error is proposed here to explain this event. This study provides evidence for reversion error as a novel mechanism for the generation of somatic mutations in human diseases. Abstract : Genetic analysis of the family with intellectual disability harboured different X‐linked KDM5C mutations.